Electric power grid resilience with interdependencies between power and communication networks – a review. Issue 2 (26th February 2020) - Liu, Xin; Chen, Bo; Chen, Chen; Jin, Dong
Abstract : Because of the development of smart grid technology, today's power grid infrastructures are increasingly and heavily coupled with communication networks for many new and existing power applications. The interdependent relationship between the two systems, in which power control relies on the communication system to deliver control and monitoring messages and network devices require power supplies from the electrical grid, brings challenges in the effort to build a highly resilient integrated infrastructure. In this work, the authors summarise existing research on power grid resilience enhancement with the consideration of the interdependencies between power systems and communication networks. They categorise these works according to stages of resilience enhancement (i.e. failure analysis, vulnerability analysis, failure mitigation, and failure recovery) and methodologies (i.e. analytical solutions, co‐simulation, and empirical studies). They also identify the limitations of existing works and propose potential research opportunities in this demanding area.